Return to play following meniscal repair - Wiley, T. J.; Lemme, N. J.; Marcaccio, S.; Bokshan, S.; Fadale, P. D.; Edgar, C.; Owens, B. D. (Clinics in Sports Medicine, 2020)
Meniscal injuries in athletes present a challenging problem. Surgeons must balance the needs of the healing meniscus with the desire of the athlete to return to play as quickly as possible. Evidence-based rehabilitation protocols are important for ensuring a successful meniscal repair and preventing athletes from returning to play prematurely. Ultimately, however, the return to play determination requires a shared decision-making approach between the physician, the athlete, and the providers involved in the athlete`s rehabilitation process. This decision considers not only the athlete`s ability to meet return-to-play criteria but also their season-specific and career goals.